Global Economic Prospects 2008 Technology Diffusion in the Developing World. - World Bank.; World Bank. (Washington, D.C. : The World Bank, 2008)
Global Economic Prospects 2008: Technology Diffusion in the Developing World examines the state of technology in developing countries and the pace with which it has advanced since the early 1990s. It reveals both encouraging and cautionary trends. On the one hand, the pace of technological progress in developing countries has been much faster than in high-income countries-reflecting increased exposure to foreign technology as a result of linkages with high-skilled diasporas and the opening of these countries to international trade and foreign direct investment.On the other hand, the technology gap remains large, and the domestic factors that determine how quickly technologies spread within developing countries often stymie progress, especially among low-income countries. This year's Global Economic Prospects comes on the heels of an extended period of strong growth and a 15 year period of strong performance in much of the developing world, which has contributed to substantial declines in global poverty. While high oil prices and heightened market volatility may signal a coming pause in this process, over the longer term continued technological progress should continue to push back poverty. Rapid technological progress in developing countries has been central to the reduction of poverty in recent decades. While the integration of global markets has played and will continue to play a key role in this, future success will increasingly depend on strengthening technical competencies and the business environment for innovative firms in developing countries.
Keywords: Currencies and Exchange Rates; Debt Markets; Economic Conditions and Volatility; Economic Theory and Research; Emerging Markets; Finance and Financial Sector Development; Financial Literacy; ICT Policy and Strategies; Industry; Information and Communication Technologies; Macroeconomics and Economic Growth; Private Sector Development; Technology Industry